High-performance manufacturing enabling integrated design and processing of products: A case study of metal cutting. (November 2021) - Lei, M.K.; Miao, W.L.; Zhu, X.P.; Zhu, B.; Guo, D.M.
Graphical abstract: Highlights: High-performance manufacturing theory and methodology enables integrated design and processing. Material–product–process linking is established on the pivot role of surface integrity. Metal cutting is demonstrated from a trial-and-error approach to a knowledge-based approach. Material-oriented regularization solves the integrated design and processing inverse problem. Process signature concept is consolidated to incorporate the coupling effect of processing. Abstract: Greater integration of materials, product and processes is demanded ultimately toward a knowledge-based control of advanced manufacturing. We propose a framework of high-performance manufacturing theory and methodology to enable the integrated design and processing of a product, with a material–product–process linking developed on the pivot role of surface integrity determining the final performance. Metal cutting, as a representative process of conventional manufacturing, is demonstrated for the new development of manufacturing from a trial-and-error approach to a knowledge-based approach under the framework. A physical model of integrated design and processing is established on thermodynamics for cutting of a metastable AISI 304 austenitic stainless steel component during processing under the multi-source constraints of component geometry, material and structure, where surface integrity changes in surface residual stress and martensitic phase fraction are predicted by FEM modeling. The profound processing effect is described by process signature that derives a quantitative correlation of processing loads in effective force/power input and material loading in transferred/dissipated thermal and mechanical energies to the surface integrity changes. A material-oriented regularization (MOR) method is thus contrived as incorporating the process signature by utilizing identified characteristic correlations of high sensitivity to solve the involved inverse problems. The processing parameters of cutting speed/depth of cut and the design parameters of geometry are synergistically determined through the required surface integrity toward a desired final fatigue performance. The high-performance manufacturing overcomes the intrinsic trial-and-error limitations of conventional manufacturing, knowledgeably considering the coupling effect of processing in the design otherwise merely employed as an empirical design criterion in the past.